2015
DOI: 10.1111/jphp.12415
|View full text |Cite
|
Sign up to set email alerts
|

Role of S100A1 in hypoxia-induced inflammatory response in cardiomyocytes via TLR4/ROS/NF-κB pathway

Abstract: Our results demonstrate that S100A1 can regulate the inflammatory response and oxidative stress in H9C2 cells via TLR4/ROS/NF-κB pathway. These findings provide an interesting strategy for protecting cardiomyocytes from hypoxia-induced inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…ROS, which are mainly produced by NADPH oxidase, are commonly considered cytotoxic and can even induce cell damage in high levels ( Ray et al, 2012 ). Previous studies also have shown that ROS were implicated in TLR4-mediated immune reactions ( Zhang et al, 2016 ; Pan et al, 2017 ), and elicited a cascade of inflammatory events, such as activation of NF-κB ( Yu et al, 2015 ; Singh et al, 2016 ). In the present study, miR-181a mimics markedly suppressed the intracellular ROS accumulation in LPS-induced macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…ROS, which are mainly produced by NADPH oxidase, are commonly considered cytotoxic and can even induce cell damage in high levels ( Ray et al, 2012 ). Previous studies also have shown that ROS were implicated in TLR4-mediated immune reactions ( Zhang et al, 2016 ; Pan et al, 2017 ), and elicited a cascade of inflammatory events, such as activation of NF-κB ( Yu et al, 2015 ; Singh et al, 2016 ). In the present study, miR-181a mimics markedly suppressed the intracellular ROS accumulation in LPS-induced macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…An early study that explores the role of S100A1 in hypoxia-induced inflammatory response in cardiomyocytes has demonstrated that S100A1 treatment significantly enhanced IL-37 protein or mRNA level, which in turn could attenuate ROS and phospho-p65 NF- κ B levels. Thus, the researchers finally considered that S100A1 could regulate the inflammatory response in H9C2 cells via TLR4/ROS/NF- κ B pathway [8082]. A recent study also further confirmed that IL-37 exerts anti-inflammatory effects via TLR2/4-NF- κ B signaling pathway.…”
Section: Il-37 Exerts Anti-inflammatory Responses In Hcaecsmentioning
confidence: 99%
“…Little is known about cardiac functions of PP5. Recently, it was reported that S100 proteins can modulate PP5 functions [11] and S100A1 that amongst others interacts with the cardiac ryanodine receptor and the Ca 2+ ATPase of the sarcoplasmic reticulum (SERCA), plays an important role in the inflammatory response in cardiomyocytes [12,13]. We have previously generated and described transgenic mice with cardiac specific overexpression of PP5 and demonstrated that PP5 serves as a modulator of cardiac function [14].…”
Section: Introductionmentioning
confidence: 99%